Evaluation Of liver And Kidney Functions In Lung And Bladder Cancer Patients - Mahmood, R.A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This study was performed at Nuclear Radiation Hospital in Baghdad for the period from January 2011 to May 2011. 44 Blood samples were collected from patients suffered lung and bladder cancer and 24 samples as healthy control individuals. Routine liver functions tests were studied by measuring S.GPT, S.GOT and Kidney function was evaluated by estimation of blood urea and creatinine in serum samples of individuals studied. It was observed that the incidence of lung and bladder cancer was higher in males than females patients ( male 81.82 %, 72.73%, female18 .18%, 27.27% respectively). Insignificant difference was noted among age of lung and bladder cancer patients compared with control group. The results of biochemical analysis of lung and bladder cancer showed an increase in the mean of values of GPT, GOT, blood urea and serum creatinine among patients when compared with the healthy individuals